Migração interna populacional e sua participação no desenvolvimento regional no final do século XX - Tavares, Gilson Queiroz (2001)
The release of the first results of the 2000 Demographic Census offers an outstanding opportunity to observe Brazil's developmental standards and demographic distribution during the 1990s. It underlines the ongoing decline of birth rates nationwide, associating this with alterations in economic and spatial organization. It notes an ongoing decline in mortality rates over the past decades. Finally, with regard to migrations and spatial redistribution of the population, it emphasizes alterations in recent migratory flows and the sIowdown in growth for some metropolitan regions and areas in the Southeast, with a rei ative upswing in retention of the population in the Northeast and the shift to the North and Center-West.